PENGARUH PEMBERIAN EKSTRAK KULIT BATANG JALOH (Salix tetrasperma Roxb) DAN SERBUK DAUN SINGKONG (Manihot esculenta Crantz) TERHADAP PERTAMBAHAN BOBOT BADAN AYAM BROILER (Effect of Willow (Salix tetrasperma Roxb) Bark Extract and Cassava (Manihot esculenta Crantz) Leaf Powder Supplementation on Weight Gain of Broiler Chickens) - Hanum Harfinda; Rinidar Rinidar; T. Armansyah; Sugito Sugito; Mustafa Sabri; Winaruddin Winaruddin (Jurnal Medika Veterinaria, 2016)
This study’s purpose is to determine the effect of supplementation of willow bark extract (1000 mg/L) in drinking water and 15% cassava leaf powder in feed on broiler weight gain. This study was designed using completely randomized design (CRD) in which 20 broiler chickens were divided into four treatment groups with five broiler per each treatment. Control group (P0) was only given commercial feed, P1 (commercial feed + cassava leaf powder), P2 (commercial feed + willow bark extract), and P3 (commercial feed + cassava leaf powder and willow bark extract). Data were analyzed using analysis of variance and followed by Duncan test. The results showed that P2 significantly different (P0.01) compare to P0 and P3, and different (P0.05) from P1. Group P1 was different (P0.05) from group P3, but P3 showed no significant different (P0.05) to P0 on weight gain. whereas feed intake was similar among treatments, however food conversion was differ among treatments. In conclusion, combination of willow bark extract and cassava leaf powder could not increase broiler chickens weight gain.